Very high energy cosmic gamma radiation - Aharonian, Felix A (World Scientific, 2004)
Includes bibliographical references (p. 473-491) and index.; This book presents the motivations and highlights the principal objectives of the field, as well as demonstrates its intrinsic links to other branches of high energy astrophysics. Preference is given to three topical areas: (i) origin of cosmic rays; (ii) physics and astrophysics of relativistic jets; (iii) observational gamma ray cosmology. Also, an essential part of the book is devoted to the discussion of the principal mechanisms of production and absorption of energetic Î³-rays in different astrophysical environments, as well as to the description of the detection methods of high energy cosmic Î³-radiation.